Evaluasi Kualitas Layanan Digital Aplikasi Tomoro Coffee Terhadap Kepuasan Kaum Produktif Menggunakan Framework E-Service Quality - Vina Dewi Ramadhanty; Martiana Kholila Fadhil; Muhammad Riza Darmawan; Fauziyah Azzahro; Muhammad Andryan Wahyu Saputra; Dananjaya Endi Pratama (JSAI (Journal Scientific and Applied Informatics), 2025)
The trend of drinking coffee among productive people has impacted the growth of coffee shops in Indonesia. To strengthen its market position, Tomoro Coffee utilizes mobile applications. However, there is dissatisfaction with the quality of Tomoro Apps' digital services in reviews. This study evaluated the quality of Tomoro's digital application services using the Electronic Service Quality model. The model focuses on comprehensive digital services from technical aspects and other aspects related to user satisfaction. The assessment was conducted on students of Jember University who made transactions through Tomoro Apps. Data was collected using a questionnaire involving 100 students as research samples. The data were processed using instrument testing, classical assumption testing, and multiple linear regression analysis. An analysis of the data showed that efficiency, responsiveness, and contact positively affected user satisfaction. From the data analysis, seven dimensions of e-service quality were known to have a significant positive and negative effect and were able to explain 88.3% of user satisfaction variability. Through this study, we found that there is still a gap between expectations and application performance. Therefore, improvements in digital service quality should be made in each dimension of electronic service quality, balanced and focused on service users, so that Tomoro Coffee continues to be a competitive advantage. These findings have managerial implications for Tomoro Coffee as recommendations on each dimension of Electronic Service Quality to improve the quality of digital services and strengthen its position in the market.